A Network Analysis of Conversational News Readers on Political and Economic Zimbabwe Online Media. (2nd January 2017) - Mathe, Limukani
ABSTRACT: The Internet has a variety of media outlets which promotes users' interaction and participation on news discussion forums. Thus the reader's interaction on the commentary forum has developed into a discursive online communities that experience the interaction of old members and the continual influx of new members. Therefore, this paper analyses the connectivity and interaction of participants in a political online community found on the readers' commentary forum attached to NewZimbabwe.com . The paper uses mainly network analysis to explore the interaction of the online community members or news readers by sampling a total number of 212 commenters. The findings of this paper assert that the discursive nature of the readers' online community is argumentative, abusive and sometimes sarcastic. The news readers' interaction is stimulated by commenters' online personality traits, shared interests in the topic and messages that are offensive or provocative.